The Influence of Ambassador Brand, Buy Interest, and Testimonies On Purchase Decisions - Mega Noviana; Dr. Osly Usman, M.Bus Syst; Marsofiyati (Journal of Digital Business and Global Economy, 2025)
This research was conducted to find out and analyze how the variables of brand ambassador, job interest, and testimonials influence purchasing decisions for undergraduate Student. This study uses quantitative methods with descriptive analysis and takes measurements through an ordinal scale. The data collection technique used in this study was through a questionnaire or questionnaire which was measured using a Likert scale from a value of one to five. The data analysis technique used is using the SmartPLS (Partial Least Squares) Statistics version 3.3.9 software by performing various tests or calculations, namely Statistical Descriptive Analysis, Outer Model, Inner Model, and Hypothesis Testing. Based on the test results obtained the results that: (1) there is a positive influence between brand ambassadors on testimonials; (2) there is a positive influence between brand ambassadors on purchasing decisions; (3) there is a positive influence between buying interest on testimonials; (4) there is a positive influence between buying interest on purchasing decisions; (5) there is a positive influence between testimonials on purchasing decisions; (6) there is a positive influence between brand ambassadors and testimonials on purchasing decisions; and (7) there is a positive influence between buying interest and testimonials on purchasing decisions.